Molecular Docking Study: Targeting mycobacterium leprae ML2640 Protein Using Active Compounds from Coscinium fenestratum - Reshma P. (International Journal of Genetic Modifications and Recombinations, 2023)
Objectives: Leprosy is an infectious disease in skin, peripheral nerve and mucosa of upper airway. Around 70% of this infection is caused by Mycobacterium leprae, which was discovered during1873. Multi drug therapy is used for the treatment, still multiple drug resistance and reactions has been reported among patients. Hence, this work focused on identifying bioactive compounds from Coscinium fenestratum that can target mycobacterium leprae ML2640 protein by in-silico approach. Method: In this study, 80 phytocompounds from Coscinium fenestratum were screened against ML2640 proteins of Mycobacterium leprae from PubChem and PDB database were docked using h PyRx tool. Pharmacological studies were analysed using Swiss ADME and ADMET tools by applying Lipinski rule. Results: Molecular docking studies that conducted on seven selected phytocompounds among 80 phytocompound from Coscinium fenestratum, demonstrating their potential binding affinity to inhibit the activity of ML2640, thereby effectively disrupting the survival, virulence, and host infection rate of the target pathogen. Pharmacological analysis utilizing Swiss ADME and ADMET analysis confirmed the drug-like properties of these phytocompounds, Conclusion: This study is highlighting these seven phytocompounds are potential as valuable candidates for further drug development against Mycobacterium leprae infection.
Keywords: ADME; ADMET; Coscinium fenestratum; ML2640; mycobacterium leprae; pharmacological analysis